2016
DOI: 10.1186/s40643-016-0103-y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of Acacia lignin-gelatin film for its possible application in food packaging

Abstract: Background:The aim of the present investigation was to develop Acacia lignin-gelatin (LG) blended films using glycerol as plasticizer and to establish correlation between lignin contents and structure, thermal and mechanical properties of the film. Acacia lignin extracted by alkali method was used for the preparation of LG blended films by solution casting method.Results: Solubility and swelling tests of the films concluded that the lignin incorporation reduced water affinity of film. Lignin incorporation prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 35 publications
5
28
0
1
Order By: Relevance
“…Similar results were observed for starch/lignin films (Bhat et al, 2013), gelatin-lignosulfonate films (Núñez-Flores et al, 2012), gelatin/lignin films (Aadil et al, 2016a) and alginate/lignin films (Aadil et al, 2016b), being the film solubility approximately 33%, 41%, 65% and 45% lower, respectively, than the control films. On the other hand, Shankar et al (2015) obtained agar/lignin films with higher solubility than agar film (control).…”
Section: Moisture Content and Water Solubilitysupporting
confidence: 74%
See 3 more Smart Citations
“…Similar results were observed for starch/lignin films (Bhat et al, 2013), gelatin-lignosulfonate films (Núñez-Flores et al, 2012), gelatin/lignin films (Aadil et al, 2016a) and alginate/lignin films (Aadil et al, 2016b), being the film solubility approximately 33%, 41%, 65% and 45% lower, respectively, than the control films. On the other hand, Shankar et al (2015) obtained agar/lignin films with higher solubility than agar film (control).…”
Section: Moisture Content and Water Solubilitysupporting
confidence: 74%
“…Similar results were observed by Spiridon et al (2011) in starch/lignin films and according to them, can be assigned to the inter-component H-bonding, which may, in turn, improve the thermal stability of the films. Aadil et al (2016a) also reported enhanced thermal stability of the lignin/gelatin films. On the other hand, the thermal stability of alginate films decreased with the incorporation of lignin (Aadil et al, 2016b).…”
Section: Thermal Behaviormentioning
confidence: 90%
See 2 more Smart Citations
“…Різні види лігніну мають здатність поглинати УФ-випромінення. Ця властивість, разом із властивістю зменшувати набухання і водопроникність матеріалів, створює підґрунтя для отримання нових пакувальних матеріалів, які не були б чутливими до умов навколишнього середовища [22,23]. [9] Лужний [9] Oganocell [9] Alcell [9] Методи розділення Лігнін характеризується термопластичністю, і ця властивість може бути покращена завдяки селективній етерифікації фенольних гідроксильних груп лігніну [24].…”
Section: властивості лігніну залежно від умов отриманняunclassified